2015
DOI: 10.1099/vir.0.000217
|View full text |Cite
|
Sign up to set email alerts
|

Virus replication cycle of white spot syndrome virus in secondary cell cultures from the lymphoid organ of Litopenaeus vannamei

Abstract: The replication cycle of white spot syndrome virus (WSSV) was investigated in secondary cell cultures from the lymphoid organ of Litopenaeus vannamei. The secondary cells formed a confluent monolayer at 24 h post-reseeding, and this monolayer could be maintained for 10 days with a viability of 90 %. Binding of WSSV to cells reached a maximum (73¡3 % of cells and 4.84¡0.2 virus particles per virus-binding cell) at 120 min at 4 8C. WSSV entered cells by endocytosis. The co-localization of WSSV and early endosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…It is known that the hemocytes are originally developed in the Hpt and are finally released from this tissue into the blood circulation in crayfish 10 11 . Furthermore, a later study proposed a model of WSSV replication in primary cell cultures from the lymphoid organ of Litopenaeus vannamei , in which the viral replication cycle is approximately 12 h, and progeny virions are produced and released at the final stage of infection 12 . Together, these findings have advanced our understanding of WSSV infection.…”
mentioning
confidence: 99%
“…It is known that the hemocytes are originally developed in the Hpt and are finally released from this tissue into the blood circulation in crayfish 10 11 . Furthermore, a later study proposed a model of WSSV replication in primary cell cultures from the lymphoid organ of Litopenaeus vannamei , in which the viral replication cycle is approximately 12 h, and progeny virions are produced and released at the final stage of infection 12 . Together, these findings have advanced our understanding of WSSV infection.…”
mentioning
confidence: 99%
“…This suggested that silencing of Pm VRP15 caused an accumulation of WSSV DNA in nucleus. It was previously reported that WSSV DNA started to be synthesized from 6 hpi and the progeny WSSV were released from 12 hpi and peaked at 18 hpi 25 . It is possible that Pm VRP15 plays a role in viral exit from the nucleus, and that when Pm VRP15 was absent, the newly synthesized viral genomes accumulated in the nucleus.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, Li et al . 25 proposed that the virus enters the cell via endocytosis and viral particle disassembly begins in the early endosome. The free nucleocapsid then injects the viral genome via a nuclear pore within the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…This process resembles well the early stage of a WSSV infection of secondary cells of the lymphoid organ as earlier demonstrated by Li et al . (). However, the uptake of WSSV by haemocytes of penaeid shrimp did not result in efficient expression of new viral proteins.…”
Section: Discussionmentioning
confidence: 97%
“…Primers were designed in a conserved region of the VP19 coding sequence using the Primer3Plus website (Li et al . ). The VP19 DNA fragment was amplified in a 50 μL of polymerase chain reaction mixture using the primers designed previously in our laboratory (forward primer 5′‐ATTGGTATCCTCGTCCTGGC‐3′ and reverse primer 5′‐GTTATCGTTGGCAGTGTCGTC‐3′).…”
Section: Methodsmentioning
confidence: 97%